Optimizing Land Acquisition Services Based on Involvement and Collaboration Between Group Governments and Communities in Telaga Bertong Subdistrict, West Sumbawa Regency - Prihatini, Yulia; Zulkiflimansyah, Zulkiflimansyah; Suparman, Suparman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The provided text discusses the complex and often controversial issue of land acquisition in Indonesia, particularly the challenges associated with land clearance for public purposes. It highlights the tension between the state's guarantee of individual land ownership and the government's responsibility to pursue infrastructure development, which may sometimes require sacrificing individual interests. The importance of public interest, as defined by the social function of land, is emphasized alongside individual economic interests. The role of the Telaga Bertong Village government in addressing land acquisition issues is described, specifically mentioning the provision of 24-hour services through social media. The research methodology used is qualitative descriptive, employing data collection techniques such as depth interviews and observations, as well as snowball sampling design. Data analysis follows Miles and Huberman's model, involving data reduction, presentation, and interpretation. The research findings indicate the involvement of community groups (Kaling, RT) in land clearance, with supporting factors including cooperative actions between the community and the government. However, challenges include the absence of compensation and reluctance from some individuals to contribute their land. The government's role in addressing these obstacles involves socialization, inventorying, and negotiations. The researcher suggests increasing the number of research subjects and ensuring the involvement of non-formal community groups in land clearance, backed by legally binding Land Clearance Team decrees. Additionally, the public service innovation in land clearance at Telaga Bertong Village should be up-to-date, digitally based, and integrated with existing systems in the National Land Agency of West Sumbawa and the local government.